Accelerating Economic Value In Developing Regions: A Meta Synthesis Of AI Adoption In Indonesian Smes And Implications For North Sulawesi's Digital Ecosystem - Taroreh, Stefen R. A.; Makhfudi; Wahyuningsih; Wasilu, Irfan H. (Yayasan Bina Lentera Insan, 2025)
The integration of Artificial Intelligence (AI) into Small and Medium Enterprises (SMEs) offers a pathway to economic acceleration, yet a significant